Penyuluhan manajemen sampah non organik pada Yayasan pendidikan Muhammad Sholahuddin Kelurahan Rawa Buntu Kecamatan Serpong Kota Tangerang Selatan. - Yusuf Supardi; Oki Iqbal Khair; Khuzaeni Khuzaeni (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The domestic waste issue in South Tangerang City, reaching 1,000 tons daily, stems from low household sorting awareness. This Community Service (PKM) activity aimed to build family awareness in independently sorting and managing organic and non-organic waste. The target audience included students' parents, foundation administrators, and community leaders at the Muhammad Sholahuddin Educational Foundation, Rawa Buntu, Serpong. The implementation method utilized a participatory approach consisting of field preparation, partner coordination, interactive counseling (lectures and Q&A), and practical simulations. Educational materials focused on household waste management, Waste Bank systems, TPS-to-TPA flows, and the 3R (Reduce, Reuse, Recycle) principles. Participants were trained to convert non-organic waste into creative pots or ecobricks and to construct stacked-bucket composters using EM4 to process food waste into liquid and solid organic fertilizers. The results showed an increase in participants' conceptual knowledge and practical skills in identifying plastic recycling codes and managing domestic waste. Through this mentoring program, the local community is now capable of sorting waste directly from the source to achieve sustainable environmental preservation.